2014
DOI: 10.1017/s0033822200050360
|View full text |Cite
|
Sign up to set email alerts
|

Dendroclimatology in the Eastern Mediterranean

Abstract: Dendroclimatology in the Eastern Mediterranean (EM) region has made important contributions to the understanding of climate variability on timescales of decades to centuries. These contributions, beginning in the mid-20th century, have value for resource management, archaeology, and climatology. A gradually expanding treering network developed by the first author over the past 15 years has been the framework for some of the most important recent advances in EM dendroclimatology. The network, now consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The NAO mode is negatively correlated with precipitation, and scPDSI across most of the basin (Figure ) and at the decadal scale is associated with same‐sign wet season (boreal winter) precipitation anomalies from Morocco and the Iberian Peninsula through western and central Anatolia, with opposing anomalies in the Levant [ Mariotti et al , ; Xoplaki et al , ]. And while there is a zonal dipole in the Mediterranean tree ring response to precipitation, with a stronger winter response to the west and an increasing spring‐summer signal in the east [ Touchan et al , , ], at decadal timescales at least the summer scPDSI does appear to reflect the broad‐scale forcing of precipitation anomalies associated with the NAO. This creates a basin‐wide coherence between northwestern Africa, the Balkans, and western Anatolia (Figure ) and opposite sign anomalies in the Levant during major Mediterranean drought and pluvial events (Figures ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The NAO mode is negatively correlated with precipitation, and scPDSI across most of the basin (Figure ) and at the decadal scale is associated with same‐sign wet season (boreal winter) precipitation anomalies from Morocco and the Iberian Peninsula through western and central Anatolia, with opposing anomalies in the Levant [ Mariotti et al , ; Xoplaki et al , ]. And while there is a zonal dipole in the Mediterranean tree ring response to precipitation, with a stronger winter response to the west and an increasing spring‐summer signal in the east [ Touchan et al , , ], at decadal timescales at least the summer scPDSI does appear to reflect the broad‐scale forcing of precipitation anomalies associated with the NAO. This creates a basin‐wide coherence between northwestern Africa, the Balkans, and western Anatolia (Figure ) and opposite sign anomalies in the Levant during major Mediterranean drought and pluvial events (Figures ).…”
Section: Discussionsupporting
confidence: 53%
“…To date, however, there is little consensus across these different records regarding the character and dominant drivers of drought variability across the basin over the last millennium. In particular, there are extant uncertainties regarding how widespread droughts are in the Mediterranean [ Roberts et al , ], the magnitude and timing of long‐term trends and centennial‐scale variability [ Esper et al , ; Touchan et al , ; Wassenburg et al , ], and how seasonal signals and large‐scale climate modes are reflected in proxy reconstructions [ Touchan et al , , ; Seim et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…This collection has advanced dendrochronology (creation and use of tree-ring sequences for dating), and it has yielded accurate, continuous dating sequences spanning over 2,000 y in the American Southwest (17) and potentially, over 10,000 y in the White Mountains of California (18). Other long sequences (8,000 to 10,000 y) exist for the Aegean, the Balkans, and the eastern Mediterranean (17,(19)(20)(21). Tree-ring specimens curated at the LTRR and at over 10 other tree-ring laboratories and research centers worldwide also are used for dendroarchaeology (the study of the interrelationships between past climate and human cultures), dendroclimatology (the study of former climates), and dendroecology (the study of past forest ecosystems, including impacts from fire, hurricanes, and other events) (22).…”
Section: Legacy Collections In Actionmentioning
confidence: 99%
“…The basic principles of tree-ring research (Bannister 1963) have been successfully demonstrated for C. libani, the most common timber import, within the circumstances encountered in Egypt. Liphschitz 2007;Touchan and Hughes 2009;Touchan et al 2011;Griggs et al 2013). (see Bardinet [2008] for thorough discussions of each), so these genera should prove similarly useful in Egypt (e.g.…”
Section: Is Dendrochronology Possible For and In Egypt?mentioning
confidence: 99%
“…However, none of the Egyptian varieties has undergone a thorough evaluation. Gourlay 1995aGourlay , 1995bEshete and Ståhl 1999;Touchan and Hughes 2009;Nicolini et al 2010;Wils et al 2010Wils et al , 2011. it appears not to form annual rings), it should still be evaluated as a potential source, given that on many occasions studies have revealed that genera/species once thought not useful for dendrochronology can in fact yield a wealth of information (e.g.…”
Section: Is Dendrochronology Possible For and In Egypt?mentioning
confidence: 99%